Experimental study of properties for sand brick with palm oil clinker as a partial replacement for fine aggregate with ratio 7.5%, 12.5% and 17.5% - Nur Afifah Adilah, Yaakob (2018)
Research has diverged from the production of sand brick to the utilization of abundantly available waste materials as aggregate replacement by using palm oil clinker (POC). This report presents experimental results on properties of sand brick made of palm oil clinker (POC). POC is a by-product of palm oil industry and its utilization in sand brick production not only solves the problem of disposing this solid waste but also helps to conserve natural resources. POC were incorporated as a replacement material for fines aggregate. The ratios of POC that have been used are 7.5%, 12.5% and 17.5% by using two method of curing which are air and water curing at four different age of curing which are 3, 7, 14 and 28 days have been prepared. The compressive strength test and flexural strength test was conducted at 3,7,14 and 28 days. Whereas, for density and water absorption would be test at 28 days. The results shows that the best ratio of POC is 12.5% for both air and water which enhances both compressive strength and flexural strength performance of the brick. The density and water absorption of the brick increases slightly when increasing the ratio of POC. This study is also expected to offer some guides and directions for upcoming research works on the incorporation of POC.